Pengaruh Brand Image Presepsi Harga Dan Kualitas ProdukTerhadap Minat Pembelian Minyak Goreng (Studi Empiris Pada Pembeli Minyak Goreng Gading Mas Ditoko Hadi Jaya) - Muhammad Ishomuddin; Agus Widarko; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the effect of brand image, perceived price and product quality on purchasing intentions of ivory mas cooking oil. This research uses consumer studies at the Hadi Jaya store in Malang City. The data obtained in this study by distributing questionnaires to consumers of ivory mas cooking oil at the Hadi Jaya shop. This study used a purposive sampling method using the slovin formula to determine the number of samples and it can be seen that the number of samples is 90 respondents. The analytical method in this study is the research instrument test (validity test, reliability test), normality test, classic assumption test (multicollinearity test, heteroscedasticity test), multiple linear regression analysis, hypothesis testing (F test, t test) and processing determination coefficient test the data used SPSS 26. The results of this study indicate that brand image, price perceptions and product quality simultaneously influence the purchase intention of ivory cooking oil. Meanwhile, brand image, price perception and product quality simultaneously and partially affect the purchase intention of ivory mas cooking oil. Keywords:: Brand image, price perception and product quality.